O008 Triage review: Should they stay, or should they go?. (30th June 2016) - Currie, Susanna; Nicol, Elizabeth; Schembri, Gabriel
Abstract : Background: BASHH guidance for GUM services advises access within 48 hours for all and on the day review for emergencies. GU services have varying policies for when capacity is reached, ranging from 'closed door' policies to triaging all, however, there are concerns that patients with significant infections may be turned away. Since 2010 our inner city clinic has used triage forms. Aims: To investigate the burden of STIs in individuals who were turned away after triage, and assess the efficacy of our triage system Methods: Review of all triaged patients between 5/1/15–24/3/15. Results: 698 patients triaged: 359M; 336F; 3 unknown. Median age 23 years (range 16–86). 488 (70%) were turned away: 255M; 230F; 3 unknown; median age 23 years (range 16–73). Warts/lumps/bumps (15%), urinary symptoms (15%) and abnormal discharge (15%) were the most common presenting symptoms and most likely to be turned away. Conclusions: Turned away patients who re-attended had a significant number of STIs and BASHH concerns are justified. Patients who never return heighten these concerns. Management of excess demand in the current financial climate is challenging, but closer links between clinics in a region, central booking systems and social media could help to direct individuals to clinics with availability.